Financial inclusion and economic status of the states of India: An empirical evidence. (18th December 2020) - Ghosh, Shantanu; Sahu, Tarak Nath
Abstract: Financial inclusion, especially for a developing nation like India, plays a vital role in framing policies to ensure the development of the underprivileged. Applying the maximum–minimum technique for normalization and inverse of the Euclidean distance for consolidation, the present study attempts to construct an index of financial inclusion across all the states and union territories of India for 2003–2018. It further explores the effect of regional classifications and productivity on the achievement of financial inclusion. Analysis suggests Chandigarh be placed at the top in terms of mean financial inclusion scores for the study period. In addition, comparison among the regional classifications advocates for significant differences. Whereas the difference between the groups based on productivity remains nonsignificant. Theoretical propositions expect uniform achievement in financial inclusion among the states of a country. However, certain macroeconomic and other factors seem to reduce the esteemed equity.